Pelatihan Dasar Aplikasi Editing Video Sebagai Pendukung Pembelajaran Bagi Guru Smp Islam Al-Azhar 22 Sentra Primer Jakarta - Wini Tarmini; Imam Safi'i; Raudhatul Jannah; Fauzi Afriansyah; Sobri Sobri (Jurnal Pengabdian Pada Masyarakat, 2022)
BASIC TRAINING OF VIDEO EDITING APPLICATIONS AS LEARNING SUPPORT FOR TEACHERS OF SMP ISLAM AL-AZHAR 22 CENTRA PRIMER JAKARTA. The purpose of this training is to provide knowledge and skills to the teachers of SMP Islam Al-Azhar 22 Centra Primer Jakarta in editing videos using the Filmora application. This training activity is carried out using a procedure consisting of three stages, namely 1) initial activities, in the form of exploration through initial tests, 2) core activities in the form of modeling, constructing together and constructing independently, 3) Final activities, namely in the form of confirmation. through knowledge and skills tests. The training that has been carried out has been able to improve the knowledge and skills of the teachers of SMP Al-Azhar 22 Centra Primer Jakarta regarding the use of the Filmora application for video editing. This training activity needs to be carried out further so that the knowledge and skills of teachers in editing videos as learning media can continue to increase.